Association between treatment for gonorrhoea and chlamydia and lower condom use in a cross-sectional study of female sex workers in southern India - Legendre-Dugal, Marianne (BMJ Open, 2016)
OBJECTIVES: To assess whether having received grey packets containing treatment for gonorrhoea and chlamydia was associated with condom use among female sex workers (FSWs) in 5 districts of southern India covered by the Avahan programme where both periodic presumptive treatment (PPT) and syndromic management were used to control these sexually transmitted infections (STIs) among FSWs. SETTING: Cross-sectional study of FSWs recruited in the field in 5 districts of southern India (Bangalore, Belgaum, Bellary, Guntur and Mumbai) in 2006–2007. PARTICIPANTS: 1378 self-identified FSWs out of 1442 were approached to participate in the study (participation rate: 95.6%). The only exclusion criterion was to be aged <18 years. PRIMARY AND SECONDARY OUTCOME MEASURES: Consistent condom use (CCU) with new or occasional clients, and with the most recent repeat client as assessed using a questionnaire administered through face-to-face interviews. RESULTS: Using the Poisson regression to model the association between the number of grey packets received in the past 3–12 months and reported CCU, adjusting for factors associated with condom use and other potential confounders in our data, CCU was lowest among FSWs who had received ≥3 grey packets in the past 3–12 months with their new or occasional clients (adjusted prevalence ratio (APR): 0.70, 95% CI 0.57 to 0.84, p<0.001) and with the most recent repeat client (APR 0.63, 95% CI 0.51 to 0.78, p<0.001). Tests for trends showed that CCU with both types of clients decreased with the number of grey packets received (p<0.001). CONCLUSIONS: Since we could not distinguish grey packets used for PPT from those given for syndromic management, these results could be either due to a perception of protection conferred by PPT or by the fact that inconsistent condom users are more at risk for STIs. Further research on the potential disinhibiting effect of PPT is warranted.